Changes in ventilator settings and ventilation–induced lung injury in burn patients—A systematic review. Issue 4 (June 2020) - Glas, Gerie J.; Horn, Janneke; van der Hoeven, Sophia M.; Hollmann, Markus W.; Cleffken, Berry; Colpaert, Kirsten; Juffermans, Nicole P.; Knape, Paul; Loef, Bert G.; Mackie, David P.; Malbrain, Manu; Muller, Jan; et al.
Highlights: There is a high variety in mechanical ventilation practices in burn patients. A trend towards implementation of lung protective ventilation is noticeable. It remains unclear whether burn patients benefit from protective ventilation. Abstract: Objective: Ventilation strategies aiming at prevention of ventilator–induced lung injury (VILI), including low tidal volumes (VT ) and use of positive end–expiratory pressures (PEEP) are increasingly used in critically ill patients. It is uncertain whether ventilation practices changed in a similar way in burn patients. Our objective was to describe applied ventilator settings and their relation to development of VILI in burn patients. Data Sources: Systematic search of the literature in PubMed and EMBASE using MeSH, EMTREE terms and keywords referring to burn or inhalation injury and mechanical ventilation. Study selection: Studies reporting ventilator settings in adult or pediatric burn or inhalation injury patients receiving mechanical ventilation during the ICU stay. Data extraction: Two authors independently screened abstracts of identified studies for eligibility and performed data extraction. Data synthesis: The search identified 35 eligible studies. VT declined from 14 ml/kg in studies performed before to around 8 ml/kg predicted body weight in studies performed after 2006. Low-PEEP levels (<10 cmH2 O) were reported in 70% of studies, with no changes over time. Peak inspiratory pressure (PIP) values above 35 cmH2 O were frequently reported. Nevertheless, 75% of the studies conducted in the last decade used limited maximum airway pressures (≤35 cmH2 O) compared to 45% of studies conducted prior to 2006. Occurrence of barotrauma, reported in 45% of the studies, ranged from 0 to 29%, and was more frequent in patients ventilated with higher compared to lower airway pressures. Conclusion: This systematic review shows noticeable trends of ventilatory management in burn patients that mirrors those in critically ill non-burn patients. Variability in available ventilator data precluded us from drawing firm conclusions on the association between ventilator settings and the occurrence of VILI in burn patients.